Effects of novel 17β-hydroxysteroid dehydrogenase type 10 inhibitors on mitochondrial respiration - Fišar, Zdeněk; Musílek, Kamil; Benek, Ondřej; Hroch, Lukáš; Vinklářová, Lucie; Schmidt, Monika; Hroudová, Jana; Raboch, Jiří (Toxicology letters, 2021)
Mitochondrial enzymes are targets of newly synthesized drugs being tested for the treatment of neurodegenerative disorders, such as Alzheimer's disease (AD). The enzyme 17β-hydroxysteroid dehydrogenase type 10 (HSD10) is a multifunctional mitochondrial protein that is thought to play a role in the pathophysiology of AD and is one of the targets of new potential AD drugs. The in vitro effects of frentizole, riluzole, AG18051, and 42 novel modulators of HSD10 (potential AD drugs) on citrate synthase (CS) activity, monoamine oxidase (MAO) activity, complex I- or complex II-linked mitochondrial respiratory rate, and complex I activity were measured in isolated pig brain mitochondria. Based on their minimal inhibitory effects on the respiratory rate of mitochondria and CS and complex I activity, six novel compounds were selected for further testing. Assuming that inhibition of MAO-B could be a desirable effect of AD drugs, only AG18051 and one new compound met the criteria for MAO-B inhibition with minimal drug-induced effects on mitochondrial respiration. In conclusion, our in vitro screening of mitochondrial effect of novel potential AD drugs has enabled the selection of the most promising molecules for further testing that are relatively safe in terms of drug-induced mitochondrial toxicity.
Keywords: Animals; Neurodegenerative Diseases; Electron transport chain; 17β-hydroxysteroid dehydrogenase type 10; Mitochondria; buněčné dýchání; Enzyme Inhibitors; Drug development; lidé; prasata; neurodegenerativní nemoci; Models, Animal; 17-hydroxysteroidní dehydrogenasy; mitochondrie; Alzheimer’s disease; Swine; inhibitory enzymů; Cell Respiration; 17-Hydroxysteroid Dehydrogenases; zvířata; Mitochondrial toxicity; Monoamine oxidase; modely u zvířat; Humans